An Exploration of the Relationship Between Patient Autonomy and Patient Advocacy: implications for nursing practice - Hyland, Deirdre (2002)
The purpose of this article is to examine whether patient/client autonomy is always compatible with the nurse’s role of advocacy. The author looks separately at the concepts of autonomy and advocacy, and considers them in relation to the reality of clinical practice from professional, ethical and legal perspectives.Considerable ambiguity is found regarding the legitimacy of claims of a unique function for nurses to act as patient advocates. To act as an advocate may put nurses at personal and professional risk. It may also be deemed arrogant and insulting to other health care professionals. Patient autonomy can be seen as a subcategory of the right of every individual to self-determination, and as such is protected by law. However, it is questionable whether the traditionally paternalistic approach to health care provision truly respects the autonomous rights of each patient.The author considers examples and cases from the literature that resulted in professional and/or personal difficulties for the nurses involved, and also reflects on an incident from her own practice where a positive outcome was achieved that demonstrated compatibility between the concepts under consideration.
Keywords: role of the nurse; patient autonomy; nursing practice; Advocacy